2008
DOI: 10.1038/ja.2008.96
|View full text |Cite
|
Sign up to set email alerts
|

A Quinoline Antibiotic from Rhodococcus erythropolis JCM 6824

Abstract: A new quinoline antibiotic, aurachin RE, was isolated and identified from a culture broth of Rhodococcus erythropolis JCM 6824. The aurachin RE structure was determined based on NMR and mass spectrometric analysis. The structure is similar to that of aurachin C antibiotics that have been identified from Stigmatella aurantiaca. Compared to aurachin C, however, aurachin RE exhibits a wide and strong antimicrobial spectrum against both high-and low-GC Gram-positive bacteria.Keywords Actinobacteria, antibiotic, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Most of this work has been pioneered by Kurosu et al 17 and Debnath et al 37 who have based much of their efforts on the creation of structures with similar SARs to aurachin RE, a natural product that shows bactericidal activity through a proposed dual mechanism of MenA and respiratory MIC (mg/mL) chain inhibition. 38 Debnath et al 37 have been able to synthesise over 400 molecules of interest with >95% purity which have been screened in bacterial growth inhibitory assays, with varying results. The compounds synthesised have been based around a benzophenone core structure, with a highly varied lipophilic side chain substitution.…”
Section: Mena: 14-dihydroxy-2-naphthoate Prenyltransferasementioning
confidence: 99%
“…Most of this work has been pioneered by Kurosu et al 17 and Debnath et al 37 who have based much of their efforts on the creation of structures with similar SARs to aurachin RE, a natural product that shows bactericidal activity through a proposed dual mechanism of MenA and respiratory MIC (mg/mL) chain inhibition. 38 Debnath et al 37 have been able to synthesise over 400 molecules of interest with >95% purity which have been screened in bacterial growth inhibitory assays, with varying results. The compounds synthesised have been based around a benzophenone core structure, with a highly varied lipophilic side chain substitution.…”
Section: Mena: 14-dihydroxy-2-naphthoate Prenyltransferasementioning
confidence: 99%
“…In an attempt at finding a new pharmacophore for MenA inhibitors, we recently identified a new quinolone natural product, aurachin RE ( 1 , Figure 3), 27 which exhibited MenA enzyme inhibitory activity as well as a wide antimicrobial spectrum against Gram-positive bacteria. As there is an overall structural resemblance between aurachin RE and our 1 st generation MenA inhibitors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly interesting that two phylogenetically unrelated species of microorganisms produce such highly structurally related secondary metabolites. Although aurachin biosynthesis genes ( aua genes) have been identified in Stigmatella, 8 our preliminary PCR screening study, based on the nucleotide and amino acid (aa) sequence data for aua , failed to identify the corresponding genes in the Rhodococcus genome 5. These results suggested that this Rhodococcus strain does not contain aua ‐type biosynthesis genes or biosynthesis genes similar to those that were isolated from Stigmatella .…”
Section: Introductionmentioning
confidence: 86%
“…We had previously isolated a new quinoline antibiotic—aurachin RE ( 1 , Scheme ), classified as group I—from a culture broth of R. erythropolis JCM 6824 5. The structure of an aurachin basically consists of a quinolone ring and a farnesyl chain, and the structure of aurachin RE is closely related to that of aurachin C (H instead of 9′‐OH), which was isolated from Stigmatella aurantiaca Sg a15 6.…”
Section: Introductionmentioning
confidence: 99%